Uncovering Norway's Regional Disparities With Respect To Natural Riches - Sevil Acar; Burhan Can Karahasan (European Regional Science Association (ERSA), 2013)
This study aims at unveiling regional development differences in Norway with respect to various natural resource-based activities that take place in the NUTS3 regions. Norway?s natural riches range from agricultural and forest resources to fisheries, mines, petroleum and gas. Considering the possible spatial links for various regional characteristics of the Norwegian economy, this study does not only reveal the wide-ranging distribution of resource-based activities, but also sheds light on divergent income and population patterns in the Norwegian regions. Besides, these patterns are investigated through a number of models that test the impact of employment, investment and value added in natural resource sectors on regional differences. The main findings suggest that mining and quarrying as well as oil and gas extraction activities generate significant advantages for regional income generation whereas each resource type affects the distribution of population in a different way.
Keywords: Q32; R12; C23; 330; natural resources; regional differences; panel data analysis